The Re-Framing of Australian Higher Education - Pick, David (Blackwell Publishing, 2006)
The aim of this paper is to analyse the changes in Australian higher education policy over the past two decades. Using frame analysis, two shifts in higher education policy are identified. The first is in the late 1980s where the view of higher education as having a broad social, economic and cultural role was changed to one that emphasised expansion, marketisation and competition. The second is currently taking place in which universities are becoming seen as business competitors in a global higher education market, and as such, privatisation and deregulation are centrally important. This paper demonstrates the usefulness of frame analysis as a way of examining the systemic effects of policy decisions in a way that draws together and uncovers how the various and complex forces of government policies and broader social and economic events combine to create the difficult terrain through which universities must now plot a course.